2021
DOI: 10.1111/pace.14408
|View full text |Cite
|
Sign up to set email alerts
|

High vagal tone predicts pulmonary vein reconnection after cryoballoon ablation for paroxysmal atrial fibrillation

Abstract: Background: Pulmonary vein (PV) isolation is an established treatment for paroxysmal drug-refractory atrial fibrillation (AF). High parasympathetic tone and reconnection of PVs have demonstrated to be possible culprits of AF recurrence after ablation.Our aim was to investigate the association between parasympathetic tone and reconnected PVs in patients with paroxysmal AF. Methods:Consecutive patients who underwent a redo catheter ablation procedure for atrial tachyarrhythmia recurrence by means of 3D electroan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Reducing overall vagosympathetic activity and minimizing imbalance between the sympathetic/parasympathetic nerve system both contributed to the prevention of AF from recurrence following catheter ablation ( 20 ). High parasympathetic tones accurately predict pulmonary vein reconnection among recurrent patients with AF receiving redo catheter ablation, no matter on vein-per-vein analysis or case-per-case analysis ( 43 ). The degree and sustained duration of parasympathetic denervation after catheter ablation were both proved related closely to AF recurrence ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reducing overall vagosympathetic activity and minimizing imbalance between the sympathetic/parasympathetic nerve system both contributed to the prevention of AF from recurrence following catheter ablation ( 20 ). High parasympathetic tones accurately predict pulmonary vein reconnection among recurrent patients with AF receiving redo catheter ablation, no matter on vein-per-vein analysis or case-per-case analysis ( 43 ). The degree and sustained duration of parasympathetic denervation after catheter ablation were both proved related closely to AF recurrence ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 A recent study has showed that intensified vagal tone estimated with DC, as well as absolute power of the very-low-frequency (VLF) band and mean of the SDs of all the NN intervals for each 5 min segment (SDNNI), was observed in ablation-treated patients with reconnected PVs compared to those without reconnections. 12 It was suggested that cardiac reinnervation, especially parasympathetic reinnervation, might be an indispensable process in reconnections of PVs, presumably accounting for the higher DC postablation in AF patients with late recurrence. In the sensitivity analysis, it was interesting that patients with early recurrence appeared to have the higher DC within the first 3 days in relation to those with late recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Regarding to late recurrence occurring after a 3-month blanking period, one of the most prominent reasons is reconnection of isolated PVs that is also associated with cardiac parasympathetic hypertonicity. 11,12 Deceleration capacity (DC), an index assessing decelerationrelated heart-rate variability (HRV), is usually regarded as an indicator of parasympathetic activity when calculated in accordance with phase-rectified signal averaging (PRSA) algorithm. 13 Owing to elimination of non-periodic components in a 24-h Holter recording, DC is rarely affected by ectopic beats and artifacts, which is superior to the established HRV parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high deceleration capacity (DC) at ECG Holter monitoring could predict AF recurrence after PVI with CB-A ( 59 ). Interestingly, high parasympathetic tone, expressed by DC and other surrogate markers, could predict not only AF recurrence but also PV reconnection ( 61 ). Right-sided only PVs reconnection was associated with higher parasympathetic tone than left-sided only PVs reconnection.…”
Section: Autonomic Denervation During Cryoballoon Catheter Ablation F...mentioning
confidence: 99%